Perdebatan antara Teks dan Konteks - Shabry, Muhammad Shadiq (Jurnal Ushuluddin: Media Dialog Pemikiran Islam, 2011)
As a crucial issue in the Qur’anic discourses , ‘text’ and ‘context’ are often contradicted. Some ulama (Islamic scholars) said that context is not necessary for understanding the Qur’an because the meaning of text became authority of readers since it has been transferred from the verbal to the textual document. While, another ulama said that context could not be avoided because it is kind of realities which was describing the meaning and the object of the text. Those controversies bring out the problem that have to solve by using historical and Qur’anic science approaches. Through content analysis, this article discovered that ‘text’ is expression of words that genuinely unchangeable to the alternative meaning. Text also means manuscript or document that has a sacral meaning. In this article, text is the versus of the Qur’an. This article also analyzes ‘context’ in which address to two meanings, ‘context’ in terms of socio-historical circumstances in time of codification of the Qur’an and ‘context’ in terms of reader circumstances. The debates occurring between ‘text’ and ‘context’ are urged by theological, linguistic, historical and sociological factors. Normally, the debate between text and context is a natural thing as long as it means compromising not seeking for contradiction, because both are possible to use parallel.